Ælfric’s Expressions for Shame and Guilt: A Study in Intra-Writer Conceptual Variation - Díaz-Vera, Javier E. (Studia Anglica Posnaniensia, 2021)
This research focuses on the analysis of onomasiological variation in Old English texts written by Ælfric; more specifically, I am interested in the study of the different motifs that shape the linguistic expressions of shame and guilt used by this Anglo-Saxon monk across different textual genres. Through the fine-grained analysis of the whole set of shame and guilt expressions recorded in the entire corpus of Ælfrician texts, a network of literal and figurative conceptualizations for each emotion is proposed here. Based on this network, I have reconstructed and analysed patterns of conceptual variation in Ælfric’s English in order to show the existing tension between literal, metonymic and metaphoric expressions for these two emotions. As shall be seen here, the introduction in Anglo-Saxon England of Augustinian psychology by Ælfric and other highly educated authors favoured (i) the progressive neglect of the Germanic concept of shame and guilt as instruments of social control, (ii) the dissemination of new shame-related values, and (iii) the growing use of a new set of embodied conceptualizations for the two emotions under scrutiny here, most of which have become common figurative expressions of shame and guilt in later varieties of English. The new expressions (e.g., SHAME IS SOMETHING COVERING A PERSON, GUILT IS A BURDEN) illustrate the shift towards a progressive embodiment of the new emotional standards brought by Christianization. According to these standards, rather than an external judgment or reproach, shame and guilt involve a negative evaluation of oneself.